Analisis Usability pada Aplikasi AntiMacet Menggunakan USE Questionnaire - calvina wuysan; Sudirman; Afifah (KHARISMA Tech, 2022)
AntiMacet is a mobile-based application in the form of an online map that provides information about the route without traffic jams to the user's destination. However, because this application has just been developed and has never been further tested, it is necessary to test the usability level. To test the usability level, we’ll use the USE Questionnaire method which has 4 aspects, namely Usefulness, Ease of Use, Ease of Learning, and Satisfaction. The study began by using questionnaires as a data collection tool. Then continued by testing the validity of the data resulting in 27 items of questions which were declared valid. After that, it continued by testing the data rehabilitation of 27 question items by generating a Cronbach's Alpha value of 0.961 and can be categorized as very reliable/ consistent. The results of this study include 4 aspects of use questionnaire, in the form of usefulness aspect with a percentage of 84.54%, ease of use aspect with a percentage of 87.76%, ease of learning aspect with a percentage of 90.90%, and satisfaction aspect with percentage of 87.18%. Thus, the overall results of this study has a percentage of 87.19%, and can be categorized as very feasible.